A contribuição do modelo FPEIR/TOPSIS no diagnóstico ambiental da segurança hídrica do médio curso do Rio Paraopeba, MG - Priscila aparecida da Rocha Honorato (2024)
The Paraopeba River Hydrographic Basin (BHRP) faces extreme climatic events and impacts from the collapse of Vale S.A. dams in Brumadinho in 2019. Integrated Water Resources Management is essential to mitigate risks, requiring joint efforts among authorities, institutions, and the community. The imminent water scarcity demands the optimization of viable solutions, highlighting the importance of Multicriteria Decision Analysis (MCDA). The DPSIR model is applied to diagnose water security in the region, allowing for the selection and classification of socio-environmental indicators. The general objective is to diagnose water security and improve the planning and management capacity of water resources in the middle course of the Paraopeba River Hydrographic Basin (BHRP) in Minas Gerais. The specific objectives aim to characterize the BHRP, select socio-environmental indicators, classify them, assess water security in the municipalities, and propose improvement solutions. The methodology of this study integrates an approach based on the DPSIR-TOPSIS model combined with the entropy weight method. This combination offers a comprehensive strategy for the sustainable management of water resources. The analysis of the municipalities in the BHRP reveals critical challenges in water resource management due to population growth, industrialization, and agricultural expansion. The classification of municipalities using the TOPSIS method highlights Brumadinho and Betim as the most vulnerable, with high rates of waterborne diseases and insufficient sewage treatment. The intense industrial and agricultural activity in these areas exacerbates the contamination of water resources, while the dam collapse in Brumadinho exemplifies the environmental risks. The study investigated the impact of the DPSIR model on diagnosing water security in the Paraopeba River Basin, MG, highlighting socio-environmental dynamics. It demonstrated the applicability of DPSIR in complex contexts, reinforcing the need for integrated approaches such as DPSIR combined with TOPSIS. The results highlighted industrial and land use pressures, indicating the need for robust public policies. The analysis of the municipalities revealed specific challenges and the importance of management plans. Data limitations were acknowledged, suggesting future local research and expansion of the DPSIR model. Proposed solutions include sustainable agricultural practices, control of acid mine drainage, and effective management policies to ensure water security and quality of life, along with infrastructure improvement, participatory management, environmental education, and climate change adaptation.